2015
DOI: 10.1002/jclp.22194
|View full text |Cite
|
Sign up to set email alerts
|

I Really Believe I Suffer From a Health Problem: Examining an Association Between Cognitive Fusion and Healthy Anxiety

Abstract: The present findings are consistent with the possibility that cognitive fusion contributes to health anxiety. Future multivariate experimental and longitudinal studies are required to establish causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Cognitive fusion was positively correlated with anxiety and depression. Other studies have found a moderate association between CF and anxiety that was not due to negative affect; moreover, this association was independent of EA [53,54]. Furthermore, a study [55] examined the mediating effect of CF in a cross-sectional design.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive fusion was positively correlated with anxiety and depression. Other studies have found a moderate association between CF and anxiety that was not due to negative affect; moreover, this association was independent of EA [53,54]. Furthermore, a study [55] examined the mediating effect of CF in a cross-sectional design.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of global distress (Bolderston 2013), depression and/or anxiety (Bolderston 2013;Cvetanovski 2014;Dinis et al 2015;Gillanders et al 2014;Kerr 2010), health anxiety (Fergus 2015), anxiety sensitivity (Solé et al 2015a), stress (Cvetanovski 2014), burnout (Gillanders et al 2014), pain-related variables (Solé et al 2015b), experiential avoidance (Dinis et al 2015;Gillanders et al 2014;Reuman et al 2016), rumination (Gillanders et al 2014;Kerr 2010;Norman 2013), paranoia (Norman 2013), body image and eating disorder symptoms (Cvetanovski 2014;Trindade and Ferreira 2014), and obsessive beliefs and COGNITIVE FUSION'S PREDICTIVE POWER OF DEPRESSIVE SYMPTOMS 3 symptoms (Reuman et al 2016). Also, cognitive fusion and rumination were found to be predictors of depression severity (Kerr 2010), and the interactive effect between cognitive fusion and experiential avoidance was also found to be a predictor of different indices of psychological distress, such as anxiety, depression, stress, and posttraumatic stress (Bardeen and Fergus 2016).…”
Section: Concurrent Effects Of Different Psychological Processes In Tmentioning
confidence: 99%
“…An opposing process of fusion occurs when such cognitive content dominates behavior by being held as literally true (Gillanders et al, 2014). Cognitive fusion has been associated with different forms of psychological distress (Ferreira et al, 2014;Fergus, 2015;Solé et al, 2015;Hapenny and Fergus, 2017), and several studies have found a relationship between cognitive fusion and depression (e.g., Zettle et al, 2011;Gillanders et al, 2014;Dinis et al, 2015;Bardeen and Fergus, 2016).…”
Section: Introductionmentioning
confidence: 99%